The importance of special safeguard tariffs (SSG) for Brazilian sugar exports - Cinthia Costa; Heloisa Burnquis; Joaquim Guilhoto (European Regional Science Association (ERSA), 2015)
This paper presents a critical analysis of the SSG and a simulation of its effects for Brazilian sugar exports to countries such as the United States (US) and the European Union (EU) bloc. A first stage involved the identification of tariff lines (TL) for the EU and the US sugar imports from Brazil during the period of 1995 to 2013. Next, WTO notifications about SSGs were examined to identify when the measure was applied for sugar by these countries at each year, since 1995. For the years that the price-based SSG applied, the value of this additional tariff was calculated for each of the relevant TLs. This information was used, with price elasticities, to obtain the corresponding change in imports. Finally, the effect of an increase in Brazilian sugar exports in the absence of SSG tariffs was calculated and also the overall impact on Brazilian economy using its input-output matrix. The results indicated that the additional tariff due to SSG catch up 90% for raw sugar in EU and 30% for white sugar in US in years 1999 and 2002, which the additional tariffs were highest. In period of 2010-2013 the SSG did not work once the sugar price was higher than trigger price in both countries. The additional tariffs applied by EU were always higher than those applied by US. We estimated that the impact of the value of sugar that was not exported to the EU and US markets due to application of SSG tariffs in period 1995-2013 was equivalent to BRL 42 billion in the production value for all economy at 2013 prices (or US 20 billion) and almost BRL 22 billion in GDP for this country. This mean that Brazil has failed to produce, in this period, almost 0.8% of its GDP due to the application of this trade policy. Considering that the SSG price-based mechanism is particularly important when international market prices are low, these results suggest that the this policy intervention can be highly perverse as it translates into decreased domestic production in both, exporting and importing countries, and dampened world prices as the excess demand is restricted.
Keywords: F13; C67; 330; Sugar; import tariff; Brazil; EU; US; input-output matrix